1994
DOI: 10.1002/ajpa.1330940405
|View full text |Cite
|
Sign up to set email alerts
|

Body dimensions and thyroid hormone levels in premenopausal and postmenopausal women from Austria

Abstract: Correlations between thyroid hormone levels and body dimensions were investigated in a group of 124 premenopausal (ages 16-40 years) and 142 postmenopausal (ages 38-61 years) women from Vienna, Austria. Twenty-nine absolute body dimensions and thirteen anthropometric indices were correlated with the serum levels of thyroxine, triiodothyronine, thyroid-stimulating hormone, and thyroid-hormone-binding globulin as well as three hormone ratios (T3/T4, T4/TSH, T3/TSH). All hormones exhibited statistically significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
3
2
1
Order By: Relevance
“…TSH elevation in women aged 47-58 compared to other age groups suggests an effect of the perimenopausal period in women in this age group. The number of studies reporting higher TSH values in the premenopausal period compared to the postmenopausal period is limited [12][13][14], although we encountered no studies assessing the perimenopausal period, and our findings are compatible with similar data from the literature. In addition, the majority of the 11 (1.9%) patients with subclinical hypothyroidism were also in this age group.…”
Section: Discussionsupporting
confidence: 91%
“…TSH elevation in women aged 47-58 compared to other age groups suggests an effect of the perimenopausal period in women in this age group. The number of studies reporting higher TSH values in the premenopausal period compared to the postmenopausal period is limited [12][13][14], although we encountered no studies assessing the perimenopausal period, and our findings are compatible with similar data from the literature. In addition, the majority of the 11 (1.9%) patients with subclinical hypothyroidism were also in this age group.…”
Section: Discussionsupporting
confidence: 91%
“…Thus it propagates the idea that in human body, post adulthood changes do occur in height. It is supported by many findings (Miall et al 1967;Roche et al 1981;Malina et al 1982;Kirchengast 1994). The most supporting relevant work staking Indian data are (Bagga 1998(Bagga , 2013Bagga and Sakurkar 2013).This type of study was mainly done in India or around the world during 1980s and 1990s and in that period, the difference was 5-7 cm (approximately) from younger to older generation, but in our study, the difference is found to be only 0.43 cm.…”
Section: Discussionsupporting
confidence: 84%
“…An inverse association between T3/T4 index and biacromial index was found (Table 3), and a similar relation has been reported for chest breadth [6]. No relations could be established here between the thyroid hormone concentrations and fat patternings (BW, BMI, % BF).…”
Section: Thyroid Hormonessupporting
confidence: 82%
“…Thus, negative correlations occurred between BW, BMI and T3 concentrations [24] whereas in other works a direct correlation was found [6,54]. In the present study performed on the Siberian sample no correlations of the anthropometric variables and indices with the thyroid hormones measured could be observed except those of the % of thigh fat.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation